Tissue localization of Drosophila melanogaster insulin receptor transcripts during development. - Garofalo, R S (1988)
The Drosophila melanogaster insulin receptor (Drosophila insulin receptor homolog [dIRH]) is similar to its mammalian counterpart in deduced amino acid sequence, subunit structure, and ligand-stimulated protein tyrosine kinase activity. The function of this receptor in D. melanogaster is not yet known. However, a role in development is suggested by the observations that levels of insulin-stimulated kinase activity and expression of dIRH mRNA are maximal during Drosophila midembryogenesis. In this study, a 2.9-kilobase (kb) cDNA clone corresponding to both the dIRH tyrosine kinase domain and some of the 3' untranslated sequence was used to determine the tissue distribution of dIRH mRNA during development. Two principal mRNAs of 11 and 8.6 kb hybridized with the dIRH cDNA in Northern (RNA) blot analysis. The abundance of the 8.6-kb mRNA increased transiently in early embryos, whereas the 11-kb species was most abundant during midembryogenesis. A similar pattern of expression was previously determined by Northern analysis, using a dIRH genomic clone (L. Petruzzelli, R. Herrera, R. Arenas-Garcia, R. Fernandez, M. J. Birnbaum, and O. M. Rosen, Proc. Natl. Acad. Sci. USA 83:4710-4714, 1986). In situ hybridization revealed dIRH transcripts in the ovaries of adult flies, in which the transcripts appeared to be synthesized by nurse cells for eventual storage as maternal RNA in the mature oocyte. Throughout embryogenesis, dIRH transcripts were ubiquitously expressed, although after midembryogenesis, higher levels were detected in the developing nervous system. Nervous system expression remained elevated throughout the larval stages and persisted in the adult, in which the cortex of the brain and ganglion cells were among the most prominently labeled tissues. In larvae, the imaginal disk cells exhibited comparatively high levels of dIRH mRNA expression. The broad distribution of dIRH mRNA in embryos and imaginal disks is compatible with a role for dIRH in anabolic processes required for cell growth. The apparently elevated expression of dIRH mRNA in nervous tissue during mid- and late embryogenesis coincides with a period of active neurite outgrowth and suggests that dIRH may be involved in this process.